Skull Repair after Major Crush Injury - H. Sudhoff; H. J. Hoff; M. Lehmann (Case Reports in Otolaryngology)
Reconstructive surgery after trauma of the head and neck is a wide field in ENT surgery. The repair of bony defects often requires implantation of engineered prostheses. We present the case of a 48-year-old male patient who had suffered a major crush injury to his head resulting in a complex bony defect. A computer-assisted designed (CAD/CAM) Titanium implant was used for reconstruction. Direct prefabrication of the individually designed implant led to an excellent coverage of the bony defect and easy adaptation to the defect margins. Results. Treatment plan and surgery as well as implant design and manufacturing were performed in a multidisciplinary team. Skin expander implantation prior to reconstructive surgery ensured a tension-free closure. This team approach led to a satisfactory outcome for this patient. This case illustrates the necessity of a multidisciplinary approach for the optimum management of complex head and neck injuries.